QUALITY OF TRANSPORTATION SERVICES BY PT. KERETA API INDONESIA (PERSERO) AT SURABAYA GUBENG STATION. FOCUS ON DIGITAL TICKET BOOKING THROUGH THE KAI ACCESS APPLICATION - Rahmawan, Alfan Dian; Rodiyah, Isnaini (Journal of Geography, Regional Planning and Development, 2024)
General Background: Transportation service quality is essential for ensuring customer satisfaction and fostering loyalty, particularly in the digital era where online platforms play a significant role. Specific Background: PT. Kereta Api Indonesia (Persero) has introduced the KAI Access application to streamline online ticket purchases and improve customer convenience, especially at Surabaya Gubeng Station. Knowledge Gap: Despite its benefits, there remain technical issues and challenges in user adoption that may impact customer perceptions and satisfaction. Understanding these challenges and identifying potential improvements is crucial. Aims: This study aims to evaluate the service quality of the KAI Access application and its impact on customer satisfaction at Surabaya Gubeng Station. Results: The findings reveal that, despite occasional technical issues, users generally perceive the application as reliable. PT KAI’s efforts, such as infrastructure improvements, responsive support via call center 121 and social media, and educational tools like video tutorials, have reduced issues and enhanced satisfaction. Additionally, professional customer service officers at Surabaya Gubeng Station further contribute to positive user experiences. Novelty: The study highlights the importance of customer education and the role of communication skills in enhancing service adoption and satisfaction. Implications: Ongoing improvements in service quality, including enhanced information provision and better handling of specific policies like ticket refunds, are essential to strengthening customer trust, satisfaction, and loyalty in the future.